Microstructural evolution and mechanical properties of near α-Ti matrix composites reinforced by hybrid (TiB+Y2O3) with bimodal size. (October 2017) - Qu, J.P.; Zhang, C.J.; Han, J.C.; Zhang, S.Z.; Yang, F.; Chen, Y.Y.
Abstract: In this study, bimodal size (TiB + Y2 O3 )/near α-Ti composites were fabricated by in situ casting route. The uniformly distributed micron TiB and micro-or nano size Y2 O3 lead to significant changes in matrix microstructure and compressive properties. With the decreasing of TiB/Y2 O3 volume ratios, significant refinement of α colony and gradual improvement of compressive strength can be obtained. As TiB/Y2 O3 volume ratio reaches 4:1, the composite displays the optimal ultimate compressive strength and ductility. And the relative strengthening mechanism along with the evolution of the compressive ductility is discussed. Highlights: Bimodal size particles reinforced titanium matrix composites are prepared. The α colony is significantly refined with decreasing of TiB/Y2 O3 volume ratios. The optimum compressive ultimate strength is 2420 MPa with ductility of 14.08%.